Editorial: Horizons of Humanity - Wit Pasierbek; Monika Grodecka (Jesuit University Ignatianum in Krakow, 2020)
The contemporary world is characterized by an extraordinary pace of global development in various spheres of life. This dynamics refers to macro, meso and micro levels of the material and spiritual world as well as to the life of an individual and social groups. Acceleration and the changes accompanying it are so great that many people find them confusing and cannot keep up. Thus the need for the fundamental questions each person must ask himself: where is it all heading? What is the aim of all this? However, in order to find the answer to these questions, it is necessary to first ask: where has it come from? And, ultimately, the question about a human being must also be asked: where has "such" a contemporary man come from? On the one hand, a human being is rational, possesses unquestionable and unique personality and dignity, is immersed in technology and computerization (including artificial intelligence), is capable of conquering the universe and treating diseases a while ago considered incurable, is affluent, possesses a lot, and lives for much longer than ever before. On the other hand, he locks himself up in his world and his 'ego', relativizes morality, psyche and relations, is addicted to impersonal matter, helpless in the face of hunger and suffering, limits the pursuit of truth to empirical facts and the verification of reason, which seems to eliminate the whole sphere of spirituality...